2022
DOI: 10.3389/fvets.2022.841406
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Wheat Bran Polysaccharides Intervention Alters Rumen Bacterial Community and Promotes Rumen Development and Growth Performance in Lambs

Abstract: There is growing interest in the utilization of plant polysaccharides for the modulation of the rumen bacterial community and enhancement of growth performance in ruminants. Fermented wheat bran polysaccharides (FWBPs), plant polysaccharides, have been shown to improve the growth performance of lambs, but little is known about their effect on rumen bacteria. The aim of this study was to investigate the effects of FWBPs supplementation to milk replacer (MR) on the growth performance, blood metabolites, weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Supplementing taurine also increased the relative abundances of Ruminococcus , NK4A214_group and Lachnospiraceae_NK3A20_group at the genus level. It was reported that Ruminococcus , 31 NK4A214_group 32 and Lachnospiraceae_NK3A20_group 33 have an important impact on the degradation of celluloses in the rumen 34 . The results of the present experiment indicated that supplementing taurine at 20–40 g d −1 tended to increase the DM digestibility and linearly increased the NDF digestibility.…”
Section: Discussionsupporting
confidence: 55%
“…Supplementing taurine also increased the relative abundances of Ruminococcus , NK4A214_group and Lachnospiraceae_NK3A20_group at the genus level. It was reported that Ruminococcus , 31 NK4A214_group 32 and Lachnospiraceae_NK3A20_group 33 have an important impact on the degradation of celluloses in the rumen 34 . The results of the present experiment indicated that supplementing taurine at 20–40 g d −1 tended to increase the DM digestibility and linearly increased the NDF digestibility.…”
Section: Discussionsupporting
confidence: 55%
“…Early studies have demonstrated that polysaccharide, saponin, or avone supplements in the diet improved the growth performance involving weight gain and feed conversion rate in animals [30][31][32] . Moreover, the bioactive substances would stimulate the development of rumen and alter its microstructure to help digestion 33 . It is well known that rumen development is very important for ruminants, and a well-developed rumen contributes to feed conversion and energy utilization 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, genera like Ruminococcus, Treponema, Butyrivibrio, and Lanchnospiraceae exhibit significant correlations with the degradation of vital nutritional components, such as CP, NDF, and ADF, across different roughage types. Moreover, specific bacteria like Rikenellaceae and Porphyromonadaceae are linked to particular roughage types, influencing the degradation rates of nutritional components [55]. These insights emphasize the integral role of rumen microorganisms in processing roughage to extract essential nutrients for the host animal [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…while Treponema and Butyrivibrio participate in volatile fatty acid (VFA) synthesis through metabolic pathways [65]. The degradation rates of nutritional components, such as CP, NDF, and ADF, are significantly associated with Ruminococcus, Treponema, Butyrivibrio, and Lanchnospiraceae.…”
Section: Discussionmentioning
confidence: 99%